2012
DOI: 10.2147/ijn.s36684
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel cationic chitosan- and anionic alginate–coated poly(D,L-lactide-co-glycolide) nanoparticles for controlled release and light protection of resveratrol

Abstract: Background:Resveratrol, like other natural polyphenols, is an extremely photosensitive compound with low chemical stability, which limits the therapeutic application of its beneficial effects. The development of innovative formulation strategies, able to overcome physicochemical and pharmacokinetic limitations of this compound, may be achieved via suitable carriers able to associate controlled release and protection. In this context, nanotechnology is proving to be a powerful strategy. In this study, we develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 74 publications
1
19
1
Order By: Relevance
“…After applying the free or nanoencapsulated trans -resveratrol to the porcine skins and then exposed to UVA radiation, they found that nanoencapsulation resulted in a larger increase in the trans -resveratrol concentrations in epidermis and dermis compared to free trans -resveratrol solution [124]. Consistent with these findings, PLGA nanoparticles significantly increased the photostability of trans -resveratrol when exposed to UVA for two hours [123]. Since trans -resveratrol is more stable than cis -resveratrol and thus has been extensively used in the studies, it is the subject of this review and is referred as resveratrol in the rest of article[122].…”
Section: Improvement Of Characteristics and Bioactivities Of Phytomentioning
confidence: 87%
See 1 more Smart Citation
“…After applying the free or nanoencapsulated trans -resveratrol to the porcine skins and then exposed to UVA radiation, they found that nanoencapsulation resulted in a larger increase in the trans -resveratrol concentrations in epidermis and dermis compared to free trans -resveratrol solution [124]. Consistent with these findings, PLGA nanoparticles significantly increased the photostability of trans -resveratrol when exposed to UVA for two hours [123]. Since trans -resveratrol is more stable than cis -resveratrol and thus has been extensively used in the studies, it is the subject of this review and is referred as resveratrol in the rest of article[122].…”
Section: Improvement Of Characteristics and Bioactivities Of Phytomentioning
confidence: 87%
“…Under UV exposure, tran -resveratrol is converted into cis -resveratrol [122]. Nanoencapsulation protects trans -resveratrol against light-exposure degradation and hence increases its stability [123,124]. Detoni CB et al compared photostability of different trans -resveratrol incorporated nanoparticles including liposomes, SLNs, nanospheres, and polymeric lipid-core nanocapsules[124].…”
Section: Improvement Of Characteristics and Bioactivities Of Phytomentioning
confidence: 99%
“…Therefore, most recent studies have counteracted the low aqueous solubility of RSV by formulating it in nanoparticles, thereby increasing the specific surface area contacting the surrounding medium45464748. Nanoparticles also have the advantage of enhanced penetration through such delivery barriers as skin49 or endothelial tissues50.…”
Section: Discussionmentioning
confidence: 99%
“…One way to mitigate the synthetic challenges that chitosan and alginate pose is to use them as surface modifiers in pre-formed nanoparticles made from a different polymer. Using this approach, researchers were able to decorate the surface of PLGA-based nanoparticles with cationic chitosan and anionic alginate to facilitate the controlled release of resveratrol (Sanna V. et al, 2012) using a layer-by-layer nanoprecipitation method (Zhou J. et al, 2010). Images of particles produced via this approach are shown in Fig.…”
Section: Methods Of Nanoparticle Manufacturementioning
confidence: 99%